A Transistor-Level Reconfigurable Circuit for Rapid Transconductor Design and Testing - Farago, P.; Festila, L.; Hintea, S.; Csipkes, G.; Csipkes, D.; Soser, P. (Elektronika ir Elektrotechnika, 2012)
In modern mixed-signal systems-on-a-chip (SoC), a key role is played by the analog filter. For intermediate frequency (IF) bands, the filtering function is best performed with Gm-C structures. The active element of Gm-C circuits is the transconductor, the design of which is particularly difficult due to the multiple and conflicting design specifications. This article proposes a reconfigurable transconductor to aid the task of transconductor design. Transistor level reconfigurability enables rapid conception, design and testing of various transconductor topologies. Extensive simulation proves the feasibility and usefulness of the proposed reconfigurable circuit. Ill. 8, bibl. 12, tabl. 5 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1062